Factors Inhibiting the Effectiveness of Enforcement Article 106 Paragraph (1) of the Traffic Law No. 22 of 2009 - Salman Haris (Estudiante Law Journal, 2021)
This study aims to the efforts of the police in tackling traffic violations Article 106 paragraph (1) of Law No. 22 of 2009 and what factors hinder the police in enforcing Article 106 paragraph (1) of Law No. 22 of 2009 is in the jurisdiction of the Satlantas Polres Gorontalo City. This research was carried out using empirical research methods that function to see the law in a real sense and examine how the law works in the community. The findings of this study are that the role of the Gorontalo City Police Satlantas Police in making efforts in tackling violations of Law No. 22 of 2009 Article 106 paragraph 1 consists of preventive and repressive efforts and the results are not maximal and comprehensive, because the target of education and socialization of knowledge of traffic rules, especially article 106 paragraph 1, is only aimed at several institutions, both schools and universities and in certain areas, but there is very little education and socialization is carried out to all elements and stakeholders who can play an active role in overcoming the number of violations traffic. The obstacles or factors faced by the police in enforcing Article 106 paragraph 1 are influenced by several factors including, law enforcement factors; the lack of police officers during operations or raids, community factors; lack of legal awareness and public knowledge about traffic rules and road transportation as well as the legal culture inherent in the community, then the factor of infrastructure; obstacles in the procurement of police posts and live traffic (cctv).